Problems of Ethno-Social Representation in Media: Review of Theoretical Approach in XX-XXI Century - Danilova, Iuliia Sokratovna; Puiy, Anatoli Stepanovich; Nikonov, Sergey Borisovich; Bekurov, Ruslan Viktorovich; Litvinenko, Anna Alexandrovna (International Review of Management and Marketing, 2015)
Several theories and researches of social science and liberal arts have been analyzed to define their place in defining specifics of cross-cultural communication. Classification of theories and comparison of research results allow making conclusions about correlation between media and social and political institutions. Today researches of ethnic-social relations in Internet may be separated into several groups by some principles. First one is researches that study ethnic nature and ethnic-social relations via texts, and works based on the study of ethnic affiliation via metadata. The second one is between research of ethnic character on the base of study of text and representation of users. Works covering the process of forming «cyberidentity» (including ethnic) should be separated from research where discourse ethnic character is considered «equal to itself» («Russian» in Internet is equal to «Russian» beyond the net). Keywords: cross-cultural communication, cyberidentity, inter-ethnic conflicts, policy of cultural diversity. JEL Classifications: O32; O33; Z13; Z18